2009
DOI: 10.3390/s90301714
|View full text |Cite
|
Sign up to set email alerts
|

Humidity Sensitivity of Multi-Walled Carbon Nanotube Networks Deposited by Dielectrophoresis

Abstract: This paper presents an investigation on the humidity sensitivity of deposited multi-walled carbon nanotube (MWCNT) networks using ac dielectrophoresis (DEP) between interdigitated electrodes (IDEs). MWCNTs dispersed in ethanol were trapped and enriched between IDEs on a Si/SiO2 substrate under a positive DEP force. After the DEP process, the ethanol was evaporated and the MWCNT network on a substrate with IDEs was put into a furnace for repeated thermal annealing. It was found that the resistance stability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(83 citation statements)
references
References 12 publications
1
81
0
1
Order By: Relevance
“…MWCNTs used in our experiments were produced by chemical vapour deposition with a diameter of 10-30 nm and a length of 10-20 m. The MWCNTs were purified through a process so-called acid treatment according to the report by Liu et al [14] The acid treatment could greatly enhance the solubility of MWCNTs by introducing carboxylic (-COOH) functional groups to the sidewalls and ends of MWCNTs. [15] Then the production of the sensor was divided into two stages.…”
Section: Sensor Production Processmentioning
confidence: 99%
“…MWCNTs used in our experiments were produced by chemical vapour deposition with a diameter of 10-30 nm and a length of 10-20 m. The MWCNTs were purified through a process so-called acid treatment according to the report by Liu et al [14] The acid treatment could greatly enhance the solubility of MWCNTs by introducing carboxylic (-COOH) functional groups to the sidewalls and ends of MWCNTs. [15] Then the production of the sensor was divided into two stages.…”
Section: Sensor Production Processmentioning
confidence: 99%
“…This process is repeated for several times until the pH of the solution reaches neutral. The acid treatment can greatly increase the solubility of MWCNTs by introducing the carboxylic functional group (-COOH) to the side wall and the tip of MWCNTs [9]. In this experiment, a multiwalled carbon nanotubes (MWCNTs) functionality process with an amino group (MWCNTs-NH 2 ) was performed under one reaction.…”
Section: Methodsmentioning
confidence: 99%
“…The use of these nano sensors also varies, some nano sensors are used for the detection of microbial contaminants [18], gas detection such as hydrogen [1,19], air humidity [7,9,20], formalin [2,16,21,22,23].Nanomaterials have a high surface area so that if used as a sensor will have a better response.However, the nanotubes in the CNT material have not been able to respond well if they have not been activated by breaking the carbon bonds on the tube wall and attached to the amino group as material functionalization so it is easy to interact with the gas. Although thismaterial provide safe detection of gas, it still have some limitations and challenges such as low relative resistance changes and selectivity, long-term instability and so on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It's found that the chemical treatment makes CNT shorten, more open ends, and more defects, which makes water molecules adsorb tubes easily and then improve the sensing performances. Liu et al [8] presented a resistor-type humidity sensor based on deposited MWCNTs networks using AC dielectrophoresis between interdigitated electrodes on silicon substrate. The sensor exhibits as a promising humidity sensing material with good reversibility, high response and good linearity, etc.…”
Section: Introductionmentioning
confidence: 99%